CYBER BULLYING DALAM PERSEPEKTIF ISLAM - Aksin, Nur; Qurrota Aini, Fiki Nu'afi (Jurnal Informatika UPGRIS, 2022)
The development of technology the internet and social media in the community at this era, is a phenomenon progress our nation. Two things that make it easier for us to getting the information and facilitate access of all things in community social dynamics. But as the other society phenomenon, besides having a positive impact, technological progress and social media right now, also have a negative impact in it. Indirectly, social media have made anonymous universe who created a kind of aggressive action of some individuals and groups to harass other people, through bad opinion and the other bad transmitting messages. This act, that known as cyberbullying, increasingly rampant. Not uncommonly, they feel safe behind anonymous account they use to hurt others. Meanwhile, about cyberbullying habit it is clear, that act (cyberbullying) are including in bullying act and bother other peopleâ€™s comfort, are prohibited in the positive law and religious law (Islamic law). So, these journals will discuss about cyberbullying at the lawâ€™s perspective, both normative and Islam .Â